Zinc deficiency may affect adolescent school girls’ perceptions - Shimizu, Toshiaki; Kawato, Chiaki; Yoshida, Noboru; Ohtomo, Yoshiaki; Niijima, Shinichi (Biomedical Research on Trace Elements, 2023)
Background: Iron and zinc are important trace elements in humans. Zinc deficiency has been reported in many studies. However, few reports have evaluated blood examinations and human behavior. Thus, this study aimed to analyze students’ exercise and daily habits and reveal their behavior combined with blood laboratory examinations during a study period of two years.Methods: This study included healthy junior and high school female students recruited from 2020 to 2021. Body height and weight were obtained by annual physical examinations, simultaneously with blood examinations. A survey was conducted on the type and frequency of exercise and daily habits. The data obtained were analyzed using a t-test, and logistic analysis was performed to compare the quantitative characteristics.Results: A total of 102 female students were included in this study. Among them, 51 students were examined twice in two consecutive years. The prevalence of iron, asymptomatic zinc (60–79 µg/dL), and symptomatic zinc (less than 60 µg/dL) deficiency was 7.8, 47.6, and 1.2%, respectively. Only one student had symptomatic zinc deficiency based on serum zinc concentration. The subject reported having rough skin and prolonged injury healing. No significant correlation was observed between serum concentration and exercise habits. Serum iron concentration was significantly higher in the extreme exercise group than that in the nonexercise group.Conclusions: Serum zinc concentration may affect adolescent girls’ perceptions of skin disorders. A higher serum zinc concentration may improve students’ quality of life by preventing skin problems.